Obesity and gut microbiota - what do we know so far? - Silva-Junior,Vicente Lopes da (2017)
In the history of medicine, only recently has obesity been recognized as a disease. We know now that it is a pandemic condition, partly explained by the so-called Western lifestyle and related to multiple other comorbidities in various systems. This lyfestyle includes eating large portions, rich in saturated fats and refined sugar, all coupled with sedentary habits. In recent years, the gut microbiota has been indited as a new culprit in pathophysiological aspects involved in obesity. From studies with animals free of bacteria in the digestive tract, known as "germ-free animals", the relevance of intestinal microbiota in the regulation of body fat became evident and its importance has also been extended to the pathophysiology of diseases such as diabetes mellitus and coronary heart disease. Characterization of Toll-like receptors led to the discovery of mechanisms that link the immune system with some metabolic pathways and opened new avenues of a previously unknown world to biological sciences. Increased knowledge about interactions between gut microbiota and the host can certainly reveal, in a not too distant future, new therapeutic perspectives for obesity and its related diseases.